Jawaharlal Nehru: the early days - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2023)
From his father he learned social etiquette from his mother, India's age-old philosophy and culture. From his Muslim mentor he learned to respect different faiths and from his English tutor the best of Western and Indian thought. But none of them could have molded the young Jawaharlal Nehru into the fiercely idealistic Indian so famous throughout the world today, that distinction he achieved by his own intelligence, keen observation and hard work.
Keywords: Visionaries; Biography- Jawaharlal Nehru; 9